2011
DOI: 10.3109/08958378.2011.575568
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry of sputum: assessing inflammation and immune response elements in the bronchial airways

Abstract: Background The evaluation of sputum leukocytes by flow cytometry is an opportunity to assess characteristics of cells residing in the central airways, yet it is hampered by certain inherent properties of sputum including mucus and large amounts of contaminating cells and debris. Objective To develop a gating strategy based on specific antibody panels in combination with light scatter properties for flow cytometric evaluation of sputum cells. Methods Healthy and mild asthmatic volunteers underwent sputum in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 32 publications
4
53
1
Order By: Relevance
“…2). In contrast to previous findings (22), the strength of these correlations was not improved by the exclusion of samples with relatively high squamous-epithelial cell contamination, or processing whole rather than selected sputum (data not shown). Neutrophils and macrophages represented a slightly greater percentage of leukocytes by DCC (medians of 30.2 and 60.8, respectively, compared to 26.0 and 57.9 by FCM; Table 2).…”
Section: Comparison Of Fcm and DCC Data In Fresh Sputum Samplescontrasting
confidence: 54%
See 1 more Smart Citation
“…2). In contrast to previous findings (22), the strength of these correlations was not improved by the exclusion of samples with relatively high squamous-epithelial cell contamination, or processing whole rather than selected sputum (data not shown). Neutrophils and macrophages represented a slightly greater percentage of leukocytes by DCC (medians of 30.2 and 60.8, respectively, compared to 26.0 and 57.9 by FCM; Table 2).…”
Section: Comparison Of Fcm and DCC Data In Fresh Sputum Samplescontrasting
confidence: 54%
“…First, the strong correlations between FCM and DCC suggest that our approach compares well (in some cases better) for identification of major leukocyte populations, compared to previous studies (13,22). Second, we measured populations before and after cryostorage.…”
Section: Discussionmentioning
confidence: 99%
“…BAL cells from healthy volunteers, which are comprised of over 80% Macs, up to 10% lymphocytes (largely T lymphocytes), and small populations of dendritic cells, neutrophils, basophils, and eosinophils (27,28), were added to the apical side of the epithelial cells, and Macs were selected by adherence ( Figure E1). Immunofluorescence analysis of the coculture indicated that the Macs became semiembedded within the 16HBE and A549 monolayers, suggesting close cell-cell interaction between Macs and epithelial cells ( Figures 1A and 1B To determine the effects of coculturing on baseline Mac immunophenotype and activity, we compared surface receptor expression and phagocytosis between air-exposed Macs in mono-versus coculture.…”
Section: Characterization Of the 16hbe-mac Coculture Modelmentioning
confidence: 99%
“…Flow cytometry was performed on BAL leukocytes for assessment of cell surface phenotypes associated with innate host defense (CD11b/CR3, mCD14, CD64/FcgRI [Fc g receptor type I]), antigen presentation/T-cell interaction (CD23/ low-affinity IgE, HLA-DR, CD86/B7.2, CD80/B7.1, CD40), and inflammation (CD16/FcgRIII). The detailed flow methodology appears in the online supplement and in our review (8). Informed consent was obtained before study and all volunteers with asthma (n = 10; age, 18-45 yr) were nonsmokers with mild to moderate disease severity.…”
mentioning
confidence: 99%
“…However, one explanation may be that IL-6-producing alveolar macrophages have become tolerant from preexisting ambient PM exposure and elevated airway inflammation, an underlying feature of asthma, thereby producing the negative association observed here after an acute exposure to PM 2. [5][6][7][8][9][10] . No change in lung function (FEV 1 , FVC) was reported after CAP exposure (Table E2), and with the exception of decreased blood IL-6 after CAP exposure (3.255 6 1.068 vs. Figures 1E and 1F); with increased expression of inflammatory receptors CD16/FcgRIII and the low-affinity IgE receptor (CD23) (Figures 1C and 1D) after CAP exposure.…”
mentioning
confidence: 99%